Composite electron emission tube fitting for 1100-1600 degrees celsius steam environment and its preparation method

CN122889644APending Publication Date: 2026-10-09JUNFENG TECHNOLOGY (NINGBO) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610905981.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-23
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0010]为克服以上现有技术的缺陷,本发明提供一种适配1100-1600℃蒸汽环境的复合电子发射管件及其制备方法,旨在同时解决现有发射管件在高温富氧蒸汽环境下易氧化剥落、高温蠕变失稳、电子发射效率不足、结构不可检修及量产一致性差的行业痛点,满足超高温蒸汽等离子锅炉长周期稳定运行的工况需求

Benefits of technology

[0016]与现有技术相比,本发明限定0.3-0.5mm的装配夹层间隙并填充氧化铝纤维与铝溶胶复合缓冲材料,能解决异种材料热膨胀系数不匹配带来的破坏性热应力问题。在1100-1600℃的升降温过程中,铁铬铝内芯与钼镧套管的热膨胀量存在差异,该缓冲层不仅吸收了由此产生的剪切应力,防止套管被挤裂或内芯弯曲,还起到了绝热和辅助支撑的作用,确保了管件在冷热循环工况下的几何尺寸稳定性与结构安全性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a composite electron emission tube fitting suitable for 1100-1600 DEG C steam environment and a preparation method thereof. The composite electron emission tube fitting adopts a three-layer composite structure of an inner layer of iron-chromium-aluminum heat accumulating matrix, a middle layer of molybdenum-lanthanum alloy protective sleeve and an outer layer of cerium boride-based metal ceramic emission layer, the sandwich is filled with buffer filler and sealed by a molybdenum-based plug to form a split type repairable structure. During preparation, a composite target material containing specific sintering additives is used for magnetron sputtering, and a segmented step curing process is combined. The application effectively overcomes the problems of matrix oxidation, coating peeling and electron emission attenuation under high-temperature water vapor environment, has excellent thermal shock stability and long-term emission performance, and is particularly suitable for extreme working conditions of steam plasma boilers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of energy-saving technology for high-temperature plasma boilers, and more specifically, to a composite electron emission tube adapted to a steam environment of 1100-1600℃ and its preparation method. Background Technology

[0002] In the fields of energy and high-end chemicals, high-temperature plasma boilers have become an important development direction for industrial heating devices due to their advantages such as high combustion efficiency and low pollutant emissions. These devices typically require long-term operation at furnace temperatures of 1100-1600℃, and the combustion chamber generally experiences high-pressure superheated steam scouring at around 350℃. Under these extreme conditions, utilizing thermionic emission materials to catalyze the ionization of the working fluid to form a plasma torch is a core technological means to achieve low-NOx fuel combustion and deep energy conservation.

[0003] However, existing high-temperature electron emission components generally suffer from irreconcilable material property conflicts and structural reliability issues when dealing with the aforementioned combined conditions of "ultra-high temperature + high humidity steam," mainly manifested in the following aspects: First, there is a contradiction between the "antioxidant properties" and "emission properties" of the material system.

[0004] Currently, mainstream high-temperature emission materials are mainly divided into two categories: refractory metals and ceramic semiconductors. Refractory metals, represented by molybdenum-lanthanum alloys, possess excellent electron emission potential, but they are extremely prone to catastrophic oxidation and ablation in high-temperature oxygen-rich steam environments. Relying solely on surface coatings for protection often fails due to interfacial reactions. Conversely, ceramic materials such as molybdenum disilicide, while exhibiting excellent self-healing and oxidation resistance, suffer from extremely low electron emission efficiency due to their inherently high work function, failing to effectively maintain stable plasma generation and significantly reducing energy-saving effects. Existing technologies struggle to simultaneously achieve high emission and long lifespan in the same device.

[0005] Secondly, structural thermomechanical failure under ultra-high temperature environments.

[0006] Within the temperature range of 1100℃-1600℃, traditional iron-chromium-aluminum alloys exhibit significant creep deformation due to dislocation slip and grain coarsening, leading to pipe collapse or blockage. High-toughness metallic materials often lack sufficient oxidation resistance, while highly oxidation-resistant ceramic materials are inherently brittle and cannot withstand the severe thermal shock during boiler start-up and shutdown. Furthermore, rigid connections (such as diffusion welding) used to achieve multi-layered protection are prone to generating enormous thermal stress during thermal cycling due to the mismatch in thermal expansion coefficients between different materials. This can lead to weld cracking or brittle fracture of the base material, and once localized damage occurs, the entire component often becomes unusable, resulting in extremely high maintenance costs.

[0007] Third, the interface degradation and process discreteness of functional coatings.

[0008] As the core of electron emission, cerium hexaboride and other boride coatings often find their grain boundaries becoming rapid diffusion channels for oxygen and water vapor under high-temperature steam erosion, leading to grain boundary corrosion and coating peeling. Although adding oxide phases can improve grain boundary properties, existing atmospheric plasma spraying or simple physical vapor deposition processes struggle to achieve a dispersed distribution of the oxide phase at the grain boundaries while maintaining high density. More critically, the lack of standardized mass production process control methods results in uneven coating thickness and large fluctuations in adhesion, failing to meet the stringent 40,000-hour stability requirements of industrial-grade products.

[0009] Therefore, developing a composite electron emission tube that can adapt to a steam environment of 1100-1600℃, integrating low-cost heat storage, high-temperature creep resistance, high-density corrosion-resistant emission, and maintainable structural design, and establishing a matching precision manufacturing process, is a technical bottleneck that urgently needs to be overcome in this field. Summary of the Invention

[0010] To overcome the shortcomings of the prior art, this invention provides a composite electron emission tube adapted to a steam environment of 1100-1600℃ and its preparation method. It aims to solve the industry pain points of existing emission tubes in high-temperature oxygen-rich steam environments, such as easy oxidation and peeling, high-temperature creep instability, insufficient electron emission efficiency, non-maintainable structure, and poor mass production consistency, so as to meet the working conditions of long-term stable operation of ultra-high temperature steam plasma boilers.

[0011] The first aspect of this invention provides a composite electron emission tube adapted to a steam environment of 1100-1600℃, comprising: The inner heat storage substrate and the protective sleeve are coaxially sleeved together, wherein the outer diameter of the inner heat storage substrate is smaller than the inner diameter of the protective sleeve, and an assembly sandwich is formed between the two. Composite buffer filler is used to fill the assembly interlayer; An activated emission layer is formed, covering the outer circumferential surface of the protective sleeve; The inner heat storage substrate is made of iron-chromium-aluminum alloy; the protective sleeve is made of molybdenum-lanthanum alloy; the activated emission layer is a metal-ceramic composite layer composed of cerium hexaboride matrix phase and alumina grain boundary reinforcing phase, wherein the alumina grain boundary reinforcing phase is dispersed at the cerium hexaboride grain boundaries.

[0012] Compared with existing technologies, this invention constructs a "ferrochrome-aluminum thermal storage inner core—molybdenum-lanthanum alloy protective sleeve—CeB" 6 / The three-layer composite structure of the "Al2O3 metal-ceramic emission layer" provides excellent heat storage capacity and low cost. The molybdenum-lanthanum alloy acts as an intermediate barrier to solve the problems of high-temperature oxidation resistance and creep resistance. The unique metal-ceramic composite layer utilizes the dispersed distribution of alumina at the cerium hexaboride grain boundaries, which not only retains the low work function of cerium hexaboride to achieve high-density thermionic emission, but also uses the ceramic phase to block the grain boundary channels, fundamentally blocking the penetration corrosion path of high-temperature steam and oxygen ions, thus achieving the best balance between material function and durability.

[0013] In one possible implementation, the mass ratio of cerium hexaboride to aluminum oxide in the activated emission layer is 94.5:5.5.

[0014] Compared with existing technologies, the above ratio has undergone optimal thermodynamic and kinetic calculations. The high proportion of cerium hexaboride ensures sufficient free electron concentration, which is the basis for achieving high emission current; while 5.5% alumina is just enough to fill the grain boundary voids and form a continuous pinned phase at the grain boundaries. This avoids blocking electron transport channels due to excessive addition and maximizes the chemical stability and structural compactness of the coating in high-temperature and water-vapor environments, thereby significantly improving plasma generation efficiency.

[0015] In one possible implementation, the thickness of the assembly interlayer is 0.3-0.5 mm, and the composite buffer filler is formed by mixing and curing alumina fibers and alumina sol.

[0016] Compared with existing technologies, this invention limits the assembly interlayer gap to 0.3-0.5mm and fills it with a composite buffer material of alumina fiber and alumina sol, which can solve the destructive thermal stress problem caused by the mismatch of thermal expansion coefficients of dissimilar materials. During the temperature rise and fall process of 1100-1600℃, there is a difference in the thermal expansion of the iron-chromium-aluminum inner core and the molybdenum-lanthanum sleeve. This buffer layer not only absorbs the resulting shear stress, preventing the sleeve from being crushed or the inner core from bending, but also plays a role in heat insulation and auxiliary support, ensuring the geometric stability and structural safety of the fitting under thermal cycling conditions.

[0017] In one possible implementation, the mass fraction of lanthanum in the molybdenum-lanthanum alloy is 0.15%.

[0018] In one possible implementation, the protective sleeve is connected to sealing plugs at both ends, the sealing plugs closing the openings at both ends of the assembly interlayer, and the sealing plugs are made of molybdenum-based alloy.

[0019] Compared with existing technologies, this invention limits the mass fraction of lanthanum in the molybdenum-lanthanum alloy to 0.15%. This specific doping amount can effectively suppress the growth tendency of molybdenum grains at high temperatures, significantly improve the recrystallization temperature and high-temperature creep resistance of the material, and ensure that the bushing does not soften or deform under long-term operating conditions of 1600℃. At the same time, with the molybdenum-based alloy sealing plug, the two ends of the interlayer are completely sealed, creating a microenvironment isolated from external oxidizing water vapor. This completely eliminates the risk of oxygen and steam intruding into the interlayer and corroding the iron-chromium-aluminum core. Moreover, the split design means that the whole unit does not need to be scrapped when there is local damage, which greatly reduces the maintenance cost throughout the entire life cycle.

[0020] In one possible implementation, the thickness of the activated emission layer is 12-18 μm, the density is not less than 98.5%, and the electron work function is not higher than 2.6 eV.

[0021] The second objective of this invention is to provide a method for preparing a composite electron emission tube, comprising the following steps: Step S1: After pre-treating the inner heat storage substrate and the protective sleeve respectively, the inner heat storage substrate is installed into the protective sleeve. The composite buffer filler is filled into the assembly interlayer and pre-cured. Then, the sealing plug is installed to obtain the workpiece. Step S2: After plasma cleaning of the workpiece, an activated emission layer is deposited using DC magnetron sputtering. The target material used is a composite sintered material of cerium hexaboride, alumina and high-purity boron powder. Step S3: Perform segmented step-high temperature curing treatment on the deposited workpiece to obtain composite electron emission tubes.

[0022] Compared with existing technologies, this invention, through the systematic control of this complete process, not only ensures the high consistency of coating thickness and bonding strength of each batch of products, meeting the needs of industrial mass production, but more importantly, through the organic combination of magnetron sputtering and subsequent step curing, successfully prepares a high-quality emitter layer with high density, strong interfacial bonding force, and no microcracks, ensuring the high reliability and stability of the product during a cumulative 40,000 hours of long-term operation.

[0023] In one possible implementation, step S1 includes preprocessing: After the outer wall of the inner heat storage substrate is polished step by step, it is degreased by ultrasonic treatment with anhydrous ethanol for 30 minutes and then dried at 180℃ for 60 minutes. The inner and outer walls of the protective sleeve were mirror polished to a roughness Ra≤0.2μm, and then vacuum annealed at 800℃ for 90min.

[0024] Compared with existing technologies, this invention thoroughly removes oxide scale, oil stains, and machining stress from the substrate surface through step-by-step grinding, ultrasonic degreasing, and high-temperature drying of the inner heat storage substrate, as well as mirror polishing and high-temperature vacuum annealing of the protective sleeve. This rigorous pretreatment process significantly enhances the physicochemical activity of the substrate surface, providing a smooth, clean base with extremely low internal stress for subsequent magnetron sputtering deposition. This greatly enhances the mechanical interlocking and physical bonding force between the activated emitter layer and the substrate, serving as the first and most important line of defense against coating peeling.

[0025] In one possible implementation, the pre-curing parameters in step S1 are as follows: temperature is 550°C and time is 120 min.

[0026] In one possible implementation, the parameters for plasma cleaning in step S2 are as follows: vacuum degree is 5.0 × 10⁻⁶. -3 The pressure is set at 180W, and high-purity argon gas with a purity of 99.999% is introduced as the working gas for 25 minutes.

[0027] Compared with existing technologies, this invention employs a 550℃ air-atmosphere pre-curing process to induce an initial ceramization transformation between alumina fibers and alumina sol fillers, forming a stable buffer layer framework with a certain strength. Subsequent plasma cleaning utilizes high-energy ions to bombard the workpiece surface, removing nanoscale adsorbed impurities and weak oxide layers, and activating surface atoms. The synergistic effect of these two steps effectively eliminates interfacial porosity in the early stages of coating growth, significantly improves the wettability between the coating and the substrate, and lays a solid physical foundation for the subsequent deposition of a dense, defect-free emitter layer.

[0028] In one possible implementation, the target material is formed by composite sintering of cerium hexaboride and alumina in a mass ratio of 94.5:5.5 as the matrix phase, and incorporating 0.3% of high-purity boron powder as a sintering aid. The parameters for DC magnetron sputtering are as follows: the base vacuum level is no higher than 4.0 × 10⁻⁶. -3 Pa, and high-purity argon gas with a purity of 99.999% is introduced as the working gas, and the working gas pressure is maintained at 0.45 Pa; The target-substrate distance is 75mm, the constant sputtering power is 220W, the workpiece substrate is kept at a constant temperature of 320℃, and a constant negative bias voltage of -85V is applied to the workpiece. The sputtering deposition time is 110-120 min.

[0029] Compared with existing technologies, this invention uses a composite target containing 0.3% boron powder and specific magnetron sputtering parameters, which not only optimizes the energy and mobility of sputtered particles and promotes the formation of a dense structure, but also the trace doping of boron activates grain boundaries and lowers the sputtering threshold. This precise process control enables the deposited coating to maintain high purity while possessing excellent microstructural uniformity and extremely low residual stress, directly determining whether the final product can achieve an ultra-high density of over 98.5% and excellent electron emission performance.

[0030] In one possible implementation, the specific steps of the segmented stepped high-temperature curing treatment in step S3 are as follows: First, heat the temperature to 380℃ at a rate of 4℃ / min and hold for 40 minutes. Then increase the temperature to 650℃ at a rate of 3℃ / min and hold for 60 minutes; Then raise the temperature to 920℃ at a rate of 2.5℃ / min and hold for 150 minutes; Finally, the furnace is cooled to room temperature at a rate not exceeding 2°C / min.

[0031] Compared with existing technologies, this invention releases the thermal stress generated during coating deposition in stages by holding the coating at different temperature ranges for extended periods. This promotes the full diffusion and rearrangement of the alumina reinforcing phase at the cerium hexaboride grain boundaries, eliminating micropores and crack sources in the coating. This treatment method greatly improves the metallurgical bonding strength between the coating and the substrate, ensuring that the finished product maintains excellent thermal shock stability with zero peeling and no cracking even under severe thermal cycling shocks from 1100°C to room temperature. Detailed Implementation

[0032] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation methods and typical parameters of the present invention, and are not intended to limit the parameter range described in the present invention. Reasonable variations derived therefrom are still within the protection scope of the claims of the present invention.

[0033] It should be noted that the endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0034] Unless otherwise defined, all terms, symbols, and other scientific terms used herein are intended to have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. In some instances, terms having a conventional meaning are defined herein for clarification or ease of reference, and such definitions should not be construed as indicating a significant difference from conventional understanding in the art. The technical methods described or referenced herein are generally well understood by those skilled in the art and employed by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents, and instruments shall be performed according to the manufacturer's instructions and parameters.

[0035] It is worth mentioning that the cerium hexaboride powder used in this invention has a purity of no less than 99.9%, and the D50 particle size is strictly controlled within the range of 1.0μm-1.5μm; the alumina used is α-type high-purity alumina with a purity of no less than 99.99% and a D50 particle size of 0.3μm-0.5μm. This specific particle size distribution design allows cerium hexaboride, as the matrix phase, to provide sufficient emission active sites, while the ultrafine alumina particles can fully fill the grain boundaries, effectively blocking water vapor permeation channels. Simultaneously, during the sintering process of the magnetron sputtering target used to prepare the coating, an additional 0.3% by mass of high-purity boron powder was added as a sintering aid. The introduction of this trace amount of boron significantly reduced the sintering densification temperature of the target, improved the conductivity uniformity and density of the target, thereby ensuring the stability of plasma discharge during subsequent sputtering deposition and the uniformity of the final coating microstructure from the source.

[0036] The following examples further illustrate this point.

[0037] Example 1 This embodiment provides a composite electron emission sleeve adapted to a 1100-1600℃ steam plasma boiler, which is prepared by the following method: Step S1: Component preparation and pretreatment A national standard 1400℃ grade heat-resistant iron-chromium-aluminum alloy was selected as the inner heat storage substrate. Its measured outer diameter is φ30mm. The outer wall of the inner heat storage substrate was polished step by step with sandpaper ranging from 240 grit to 800 grit. Then it was immersed in anhydrous ethanol for ultrasonic degreasing treatment for 30 minutes. After being taken out, it was dried in a constant temperature oven at 180℃ for 60 minutes.

[0038] A molybdenum-lanthanum alloy with a lanthanum mass fraction of 0.15% was selected as the protective sleeve, with an inner diameter of φ30.5mm and a wall thickness of 2.5mm, thus forming a 0.5mm assembly interlayer between the inner and outer tubes. The inner and outer walls of the protective sleeve were precision mirror polished to achieve a surface roughness Ra of 0.15μm. Subsequently, the protective sleeve was placed in a vacuum annealing furnace and held at 800℃ for 90min to eliminate residual stress generated by the previous machining.

[0039] Step S2, sandwich assembly and pre-curing The pretreated inner heat storage substrate is inserted into the protective sleeve in the center, ensuring that the axes of the two coincide to form a uniform assembly sandwich. The assembly sandwich is uniformly filled with a composite buffer filler made of alumina fiber and aluminum sol. Specifically, in this embodiment, the mass ratio of alumina fiber to aluminum sol is 1:1. After filling, the assembly is placed in an air atmosphere oven for pre-curing treatment. The temperature is set at 550℃ and the holding time is 120 minutes to allow the filler to initially harden and set. Then, molybdenum-based high-temperature alloy sealing plugs are welded to both ends of the protective sleeve to completely seal the openings at both ends of the assembly interlayer, forming a sealed heat-insulating buffer chamber. At this point, the workpiece preparation is complete. Step S3, Plasma Cleaning The workpiece is transferred into the vacuum chamber of the magnetron sputtering equipment, and the vacuum is evacuated to a background vacuum of 5.0 × 10⁻⁶. -3 Pa, introduce high-purity argon gas with a purity of 99.999% as the working gas, turn on the radio frequency power supply, set the power to 180W, and perform glow discharge cleaning on the workpiece surface for 25 minutes to remove trace impurities and oxide film adsorbed on the surface and activate the substrate surface. Step S4: DC magnetron sputtering deposition is performed on the substrate surface. In this embodiment, the composite sintering target is composed of cerium hexaboride and high-purity α-alumina in a mass ratio of 94.5:5.5 as the matrix phase, and high-purity boron powder accounting for 0.3% of the total mass of the matrix phase is added as a sintering aid and sintered together.

[0040] Sputtering process parameters are set as follows: target-substrate distance is 75 mm, and the background vacuum level is not higher than 4.0 × 10⁻⁶. -3 The system was operated at 0.45 Pa by introducing 99.999% high-purity argon gas and maintaining the working pressure at 0.45 Pa. A DC power supply was turned on, and a constant sputtering power of 220 W was set. Simultaneously, the workpiece substrate was heated and kept at 320 °C, while a constant negative bias of -85 V was applied to the workpiece. Sputtering deposition was continued for 115 min under these parameters, forming an activated emission layer with a thickness of approximately 15 μm on the outer surface of the protective sleeve. This activated emission layer consisted of a cerium hexaboride matrix phase and alumina reinforcement phase dispersed at the grain boundaries. Step S5: Segmented Stepped High-Temperature Curing After deposition, the workpiece undergoes in-situ heat treatment, the specific steps of which are as follows: First stage: Increase the temperature from room temperature to 380℃ at a rate of 4℃ / min and hold for 40 minutes to promote the expulsion of organic components; The second stage: the temperature is increased to 650℃ at a heating rate of 3℃ / min and held for 60min to promote the ceramicization transformation of aluminum sol. The third stage: the temperature is increased to 920℃ at a heating rate of 2.5℃ / min and held at a constant temperature for 150min to achieve interfacial diffusion and metallurgical bonding between the coating and the substrate. Fourth stage: Then, the furnace is slowly cooled to room temperature at a rate not exceeding 2℃ / min to release thermal stress to the maximum extent.

[0041] Example 2 This embodiment provides a composite electron emission sleeve adapted to a 1100-1600℃ steam plasma boiler. The main difference between this embodiment and Embodiment 1 lies in the adjustment of the sputtering deposition process parameters. Specifically, in step S4, during the DC magnetron sputtering process, the sputtering deposition time is adjusted to 110 minutes, thereby preparing an activated emission layer with a thickness of approximately 12 μm on the outer surface of the protective sleeve. Apart from this adjustment of process parameters, the specifications of other components, pretreatment, assembly, cleaning, target material composition ratio, and stepped curing process remain consistent with Embodiment 1, and will not be repeated here.

[0042] Example 3 This embodiment provides a composite electron emission sleeve adapted to 1100-1600℃ steam plasma boilers. The main difference between this embodiment and Embodiment 1 lies in the adjustment of the sputtering deposition process parameters. Specifically, in step S4, during DC magnetron sputtering, the sputtering deposition time is adjusted to 120 minutes, thereby preparing an activated emission layer with a thickness of approximately 18 μm on the outer surface of the protective sleeve. Apart from this adjustment of process parameters, the specifications of other components, pretreatment, assembly, cleaning, target material composition ratio, and stepped curing process remain consistent with Embodiment 1, and will not be repeated here.

[0043] Example 4 This embodiment provides a composite electron emission sleeve adapted to 1100-1600℃ steam plasma boilers. The main difference between this embodiment and Embodiment 1 is the use of a molybdenum-lanthanum alloy with a lanthanum mass fraction of 0.15% as the protective sleeve, with an inner diameter of φ30.3mm. Except for this adjustment of process parameters, the pretreatment, assembly, cleaning, target material composition ratio, and stepped curing process remain consistent with Embodiment 1, and will not be repeated here.

[0044] Example 5 This embodiment provides a composite electron emission sleeve adapted to 1100-1600℃ steam plasma boilers. The main difference between this embodiment and Embodiment 1 is the use of a molybdenum-lanthanum alloy with a lanthanum mass fraction of 0.15% as the protective sleeve, with an inner diameter of φ30.4mm. Except for this adjustment of process parameters, the pretreatment, assembly, cleaning, target material composition ratio, and stepped curing process remain consistent with Embodiment 1, and will not be repeated here.

[0045] Comparative Example 1 This comparative example provides a composite electron emission sleeve, which differs from Example 1 mainly in the design of the target material composition for the activated emission layer. Specifically, the activated emission layer in this comparative example does not contain alumina, and the magnetron sputtering target used is composed only of cerium hexaboride and an additional 0.3% by mass of high-purity boron powder sintered together. Except for the adjustment of the target material composition, the sleeve structure, assembly process, plasma cleaning parameters, magnetron sputtering deposition conditions, and segmented stepped curing process are all consistent with Example 1, and will not be repeated here.

[0046] Comparative Example 2 This comparative example provides a composite electron emission sleeve, which differs from Example 1 mainly in its tube structure. Specifically, this comparative example does not contain a buffer filler sandwich structure, but instead uses a gapless integrated single-layer sleeve structure with molybdenum-lanthanum alloy and iron-chromium-aluminum bonded by diffusion welding; apart from the above structural changes, the other related manufacturing process parameters are consistent with those of Example 1, and will not be repeated here.

[0047] Comparative Example 3 This comparative example provides a composite electron emission sleeve, which differs from Example 1 mainly in its tube structure. Specifically, in this comparative example, the outer layer is changed from a metal-ceramic emission layer to a conventional Al2O3-Cr2O3-La2O3 insulating ceramic coating prepared by plasma spraying; apart from the above structural changes, the other related preparation process parameters are consistent with those of Example 1, and will not be repeated here.

[0048] Comparative Example 4 This comparative example provides an electron emission tube, which differs from Example 1 mainly in that it does not include a protective sleeve. Specifically, this comparative example only uses an ODS iron-chromium-aluminum single-substrate structure, and directly sputters and deposits an electron emission surface layer with the same composition as in Example 1 on the outer surface of this substrate. Apart from this structural simplification, the remaining pretreatment, assembly, and heat treatment process parameters are consistent with those of Example 1, and will not be repeated here.

[0049] Comparative Example 5 This comparative example provides a composite electron emission sleeve, which differs from Example 1 mainly in the adjustment of the mass ratio of cerium hexaboride to alumina in the activated emission layer. Specifically, in the magnetron sputtering target used in this comparative example, the mass ratio of cerium hexaboride to alumina is set to 94:6, that is, the alumina doping amount is relatively increased. Apart from this adjustment of the target composition, the sleeve structure, assembly process, plasma cleaning parameters, magnetron sputtering deposition conditions, and segmented step-curing process are all consistent with Example 1, and will not be repeated here.

[0050] Comparative Example 6 This comparative example provides a composite electron emission sleeve, which differs from Example 1 mainly in the adjustment of the mass ratio of cerium hexaboride to alumina in the activated emission layer. Specifically, in the magnetron sputtering target used in this comparative example, the mass ratio of cerium hexaboride to alumina is set to 96:4, meaning the alumina doping amount is relatively reduced. Apart from this target composition adjustment, the sleeve structure, assembly process, plasma cleaning parameters, magnetron sputtering deposition conditions, and segmented step-curing process are all consistent with Example 1, and will not be repeated here.

[0051] Comparative Example 7 This comparative example provides a composite electron emission sleeve, which differs from Example 1 mainly in the fine-tuning of the protective sleeve alloy composition. Specifically, the molybdenum-lanthanum alloy protective sleeve used in this comparative example has a lanthanum mass fraction of 0.1%. Apart from this alloy composition adjustment, the sleeve structure, assembly process, target material composition, sputtering deposition, and curing process are all consistent with Example 1, and will not be repeated here.

[0052] Comparative Example 8 This comparative example provides a composite electron emission sleeve, which differs from Example 1 mainly in the fine-tuning of the protective sleeve alloy composition. Specifically, the molybdenum-lanthanum alloy protective sleeve used in this comparative example has a lanthanum mass fraction of 0.2%. Apart from this alloy composition adjustment, the sleeve structure, assembly process, target material composition, sputtering deposition, and curing process are all consistent with Example 1, and will not be repeated here.

[0053] Comparative Example 9 This comparative example provides a composite electron emission sleeve, which differs from Example 1 mainly in that no sintering aid is added during the magnetron sputtering target preparation process. Specifically, the target used in this comparative example is made by directly sintering cerium hexaboride and alumina in a mass ratio of 94.5:5.5, without incorporating 0.3% of high-purity boron powder by mass of the matrix phase. Except for the adjustment of the target preparation process, the sleeve structure, assembly process, plasma cleaning parameters, magnetron sputtering deposition conditions, and segmented step-curing process are all consistent with Example 1, and will not be repeated here.

[0054] Comparative Example 10 This comparative example provides a composite electron emission sleeve, which differs from Example 1 mainly in the simplification of the post-processing. Specifically, after the magnetron sputtering deposition of the activated emission layer in step S4, this comparative example omits the segmented stepped high-temperature curing process, instead directly holding the workpiece at 920°C for 150 minutes followed by furnace cooling. Apart from this adjustment in heat treatment process, the sleeve structure, assembly process, target material composition, and sputtering deposition parameters remain consistent with Example 1, and will not be repeated here.

[0055] Furthermore, this application conducted performance tests on the pipe fittings obtained in Examples 1-5 and Comparative Examples 1-10, and the test results are shown in Table 1.

[0056] Table 1 Performance Test Results Based on the test data above, it can be seen that the three-layer composite architecture of "iron-chromium-aluminum thermal storage substrate - molybdenum-lanthanum alloy protective sleeve - CeB6 / Al2O3 metal ceramic emission layer" constructed in this invention has successfully overcome the technical barriers of the incompatibility between material oxidation resistance, thermal shock resistance and high electron emission under ultra-high temperature steam environment through the synergistic coupling of multiple physical fields.

[0057] Specifically, the excellent performance of Examples 1-5 verifies the effectiveness of the core process window: the specific ratio of the metal-ceramic layer ensures high electron emission current while constructing a dense anti-corrosion barrier using the alumina phase dispersed at the grain boundaries; the 0.3-0.5mm buffer interlayer and molybdenum-based plug design effectively absorb the thermal expansion mismatch stress between dissimilar materials, allowing the pipe to maintain structural integrity during 50 rapid cooling and heating cycles. In contrast, the data from Comparative Examples 1, 5, and 6 confirm the decisive influence of alumina doping amount on grain boundary corrosion and electron transport properties; Comparative Examples 7 and 8 reveal that 0.15% lanthanum content in the molybdenum-lanthanum alloy is the optimal critical point for balancing high-temperature creep resistance and economy; and Comparative Examples 9 and 10 respectively highlight the irreplaceable role of boron powder additives in densifying the target material and segmented step-curing in eliminating residual stress in the coating.

[0058] Most importantly, compared to the integrated diffusion-welded structure of Comparative Example 2, the split-type detachable structure of this invention achieves an order-of-magnitude improvement in thermal cycling life; compared to the insulating ceramic coating of Comparative Example 3, the emission current density of this invention is increased by more than 2 times. This indicates that this invention not only achieves innovation in material composition but also breaks through the limits of traditional processes in structural design, ensuring continuous and stable operation for more than 5 years under extreme conditions of 1100-1600℃, providing a key core component solution for ultra-high temperature steam plasma boilers.

[0059] While the disclosure is as stated above, its scope of protection is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of this disclosure, and all such changes and modifications will fall within the protection scope of this invention.

Claims

1. A composite electron emission tube adapted to a steam environment of 1100-1600℃, characterized in that, include: The inner heat storage substrate and the protective sleeve are coaxially sleeved together, wherein the outer diameter of the inner heat storage substrate is smaller than the inner diameter of the protective sleeve, and an assembly sandwich is formed between the two. Composite buffer filler is used to fill the assembly interlayer; An activated emission layer is formed, covering the outer circumferential surface of the protective sleeve; The inner heat storage substrate is made of iron-chromium-aluminum alloy; the protective sleeve is made of molybdenum-lanthanum alloy; the activated emission layer is a metal-ceramic composite layer composed of cerium hexaboride matrix phase and alumina grain boundary reinforcing phase, wherein the alumina grain boundary reinforcing phase is dispersed at the cerium hexaboride grain boundaries.

2. The composite electron emission tube according to claim 1, characterized in that, The mass ratio of cerium hexaboride to aluminum oxide in the activated emission layer is 94.5:5.

5.

3. The composite electron emission tube according to claim 1, characterized in that, The thickness of the assembly interlayer is 0.3-0.5 mm, and the composite buffer filler is formed by mixing and curing alumina fibers and aluminum sol.

4. The composite electron emission tube according to claim 1, characterized in that, The mass fraction of lanthanum in the molybdenum-lanthanum alloy is 0.15%. And / or, the protective sleeve is connected to sealing plugs at both ends, the sealing plugs closing the openings at both ends of the assembly interlayer, and the sealing plugs are made of molybdenum-based alloy.

5. The composite electron emission tube according to claim 1, characterized in that, The activated emission layer has a thickness of 12-18 μm, a density of not less than 98.5%, and an electron work function of not more than 2.6 eV.

6. A method for preparing the composite electron emission tube according to any one of claims 1 to 5, characterized in that, Includes the following steps: Step S1: After pre-treating the inner heat storage substrate and the protective sleeve respectively, the inner heat storage substrate is installed into the protective sleeve. The composite buffer filler is filled into the assembly interlayer and pre-cured. Then, the sealing plug is installed to obtain the workpiece. Step S2: After plasma cleaning of the workpiece, an activated emission layer is deposited using DC magnetron sputtering. The target material used is a composite sintered material of cerium hexaboride, alumina and high-purity boron powder. Step S3: Perform segmented step-high temperature curing treatment on the deposited workpiece to obtain composite electron emission tubes.

7. The preparation method according to claim 6, characterized in that, In step S1, the preprocessing includes: After the outer wall of the inner heat storage substrate is polished step by step, it is degreased by ultrasonic treatment with anhydrous ethanol for 30 minutes and then dried at 180℃ for 60 minutes. The inner and outer walls of the protective sleeve were mirror polished to a roughness Ra≤0.2μm, and then vacuum annealed at 800℃ for 90min.

8. The preparation method according to claim 6, characterized in that, In step S1, the pre-curing parameters are as follows: temperature is 550℃, and time is 120min; And / or, in step S2, the parameters for plasma cleaning are as follows: vacuum degree is 5.0 × 10⁻⁶. -3 The pressure is set at 180W, and high-purity argon gas with a purity of 99.999% is introduced as the working gas for 25 minutes.

9. The preparation method according to claim 6, characterized in that, The target material is formed by composite sintering of cerium hexaboride and alumina in a mass ratio of 94.5:5.5 as the matrix phase, and high-purity boron powder accounting for 0.3% of the total mass of the matrix phase as a sintering aid. The parameters for DC magnetron sputtering are as follows: the base vacuum level is no higher than 4.0 × 10⁻⁶. -3 Pa, and high-purity argon gas with a purity of 99.999% is introduced as the working gas, and the working gas pressure is maintained at 0.45 Pa; The target-substrate distance is 75mm, the constant sputtering power is 220W, the workpiece substrate is kept at a constant temperature of 320℃, and a constant negative bias voltage of -85V is applied to the workpiece. The sputtering deposition time is 110-120 min.

10. The preparation method according to claim 6, characterized in that, In step S3, the specific steps of the segmented stepped high-temperature curing treatment are as follows: First, heat the temperature to 380℃ at a rate of 4℃ / min and hold for 40 minutes. Then increase the temperature to 650℃ at a rate of 3℃ / min and hold for 60 minutes; Then raise the temperature to 920℃ at a rate of 2.5℃ / min and hold for 150 minutes; Finally, the furnace is cooled to room temperature at a rate not exceeding 2°C / min.